Parotid sialolithiasis in a two-year-old boy - Do Hoon Kim; Woo Sun Song; Yeong Jin Kim; Won Duck Kim (Korean Pediatric Society, 2013)
Sialolithiasis is caused by the obstruction of a salivary gland or its excretory duct by the formation of calcareous concretions or sialoliths; this results in salivary ectasia and provokes subsequent dilation of the salivary gland. Sialolithiasis is relatively common, accounting for 30% of salivary diseases; however, it is rarely observed in childhood. This case report describes a 2-year-old male patient who complained of a painful swelling over the right cheek, and presented with palpable stones and pus discharge from the orifice of the right Stensen's duct. Computerized tomography of the neck confirmed the diagnosis, and the patient received intravenous empiric antibiotics combined with intraoral sialolithotomy. We also provide a review of the spectrum of concepts regarding the pathogenesis, diagnosis, and treatment of sialolithiasis.